The United States of America and Political Alliances in the Middle East 1935-1950 - Chibchab, Hameed Abo Lool (International Journal of Psychosocial Rehabilitation, 2020)
The period between 1935 and 1950 witnessed the period of the emergence of alliances and international treaties that some historians described as an epidemic fever, and these alliances became a concern of its governments and divisions, which led to the Arab world is preoccupied with caring for its internal affairs, especially since the Middle East after World War II was in the process of being established And with a dire need for work, construction, reconstruction, and progress, but the alliances that Western countries sought to drag the region into, whether through persuasion or through imposition and threats, all were military alliances under the pretext that they do so because they are between them and the general Middle East region and the Arab region, especially a lot of traditional relations, interests and civilization. Therefore, it is their duty to defend and preserve them.